Charivari or the Historicising of a Question. The Irrelevance of Romantic Love for the Audio-Visual Performance of Marriage in Bern in the 18th and 19th Century Charivari or the Historicising of a Question - Arno Haldemann (Journal for Religion, Film and Media, 2018)
Citing Oscar Wilde, the editors of this volume ask the question "who, being loved, is poor?" in their call for papers. On a meta-theoretical level, this article aims at contextualising this question and its citation socially. On an empirical level, it intends to contrast the socially highly determined question and its implicit presuppositions with the findings of a locally situated case study in the canton of Berne in the 18th and 19th century. By studying precarious marriages through petitions for the dispensation from the preacher's threefold reading of the banns from the pulpit, the collective audio-visual dimension of marriages in an agrarian-shaped society of scarce resources becomes apparent. With the petitions, the couples tried to avoid attention and thus, to escape the communal tribunal of a charivari and the like. In Bern, concerning the material and media dimensions, weddings were largely governed by local standards. Charivaris were the audio-visual means of society to communicate shared values regarding marriage. They did not reflect romantic ideals of love, but were an expression of the locally accentuated moral economy. The performance of weddings as large and public rituals was a communal compulsion rather than the expression of an individualistic and therefore creative event. Performative weddings as the epitome of individualism are a very young historic development and strongly linked to a late-modern bourgeois culture of singularity.